2015
DOI: 10.1123/pes.2014-0150
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-Vigorous Physical Activity and Sedentary Behavior: Independent Associations With Body Composition Variables in Brazilian Children

Abstract: This study aimed to analyze the independent associations of accelerometer-determined sedentary behavior, physical activity, and steps/day with body composition variables in Brazilian children. 485 children wore accelerometers for 7 days. Variables included time in sedentary behavior and different physical activity intensities (light, moderate, vigorous, or moderate-to-vigorous) and steps/day. Body fat percentage was measured using a bioelectrical impedance scale, and BMI was calculated. Children spent 55.7% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
4
33
1
Order By: Relevance
“…Evidence shows negative association between steps/day and MVPA (objectively measured) and adiposity 6 , 11 , 12 . Several research studies 6 , 12 , 13 have found negative relationship between steps/day and BMI and body fat percentage (%BF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows negative association between steps/day and MVPA (objectively measured) and adiposity 6 , 11 , 12 . Several research studies 6 , 12 , 13 have found negative relationship between steps/day and BMI and body fat percentage (%BF).…”
Section: Introductionmentioning
confidence: 99%
“…The use of accelerometers has become more common in research studies on physical activity in childhood in high-income countries 3 , 5 . On the other hand, there are relatively few studies that have used this technology in low-and middle-income countries, such as Brazil 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, evidence has substantially supported these associations (Ferrari et al, 2015;Nemet, 2016). In children from many countries, greater MVPA and VPA were both associated with lower odds of obesity, independently of SB (Nemet, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, higher PA levels were consistently associated with an improved metabolic profile and a reduced risk for metabolic syndrome and/or insulin resistance (IR) (Guinhouya, Samouda, Zitouni, Vilhelm, & Hubert, 2011). Inverse associations between obesity and PA were also highlighted (Ferrari et al, 2015;Nemet, 2016). Among normal weight youth, those with relatively high levels of PA tend to have less adiposity than youth with low PA levels (CDC, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, De Moraes et al (2015) examined the associations between physical activity and body composition in 485 Brazilian children and found that both moderate-to-vigorous and vigorous physical activity was negatively associated with body composition (BMI and body fat percentage) variables. Duncan et al (2006) also found a link between physical activity and body fat in 1115 children from New Zealand (536 boys, 579 girls) aged 5-12 years, like has been observed in the present paper.…”
Section: Discussionmentioning
confidence: 99%